PENGARUH PERAN PEMERINTAH DAERAH DAN AKSES PERMODALAN TERHADAP PENGEMBANGAN UMKM PADA AHAD FESTIVAL KOTA LHOKSEUMAWE - Rizky Khairunna; Lianti; Diana (STKIP Subang, 2026)
This study aims to determine the effect of local government role and capital access on the development of Micro, Small, and Medium Enterprises (MSMEs) in Lhokseumawe City. The research method was conducted using multiple linear regression testing with primary data, and the sample obtained through non-probability sampling technique was 95 respondents. The respondents are MSME actors at Ahad Festival in Lhokseumawe City. Primary data were collected through questionnaires using Google Form, while secondary data were obtained from official documents of related institutions and BPS. The partial test results (t) show that the Local Government Role variable (X1) has a positive and significant effect on MSME Development in Lhokseumawe City. The Capital Access variable (X2) also has a positive and significant effect on MSME Development in Lhokseumawe City. Simultaneously (F test), it shows that the Local Government Role and Capital Access variables together have a positive and significant effect on MSME Development in Lhokseumawe City. In addition, the Adjusted R Square value is 0.690. This means that the local government role and capital access variables together are able to explain 69% of the variation in MSME development, and the remaining 31% is influenced by other factors outside this research model.